Pre-genetic Diagnosis (PGD): a Covered Eugenics? (Revista Iberoamericana de Bioética, 2019)
In the last decade, there has been an increase in reproductive technologies, especially Pre-implantation Genetic Diagnosis (DGPI): the selection of healthy embryos obtained through in vitro fertilization programs before they are transferred to a maternal uterus. Genetic improvement may lead to positive eugenics, which exclude certain illnesses, or negative eugenics, which opens up room for parents to choose child-specific characteristics such as skin, eye color, or level of reasoning. From the notion of vulnerability and need for embryo protection, it is argued that measures should be taken before severe damage arises.
Keywords: DGPI; genetic mapping; genetic improvement; eugenia